Enhancing healthy sexual practices among Iranian adolescent girls: evaluating an educational programme based on the theory of planned behavior - Fateme Badiei; Mohammad Hossein Kaveh; Abdolrahim Asadollahi; Elahe Zare; Ahmad Ghanizadeh (International Journal of Adolescence and Youth)
Comprehensive sexual health education is crucial for adolescents and should align with cultural values. This study assessed the impact of a Theory of Planned Behavior (TPB)-based educational programme on sexual behaviours among Iranian adolescent girls. A quasi-experimental design involved 236 high school girls aged 15–17, divided into experimental and control groups via multistage cluster sampling. The experimental group attended eight interactive sessions and received materials via WhatsApp over two months. Data were collected using a TPB-based questionnaire before and after the intervention. Post-intervention, significant improvements were observed in all TPB constructs except perceived behavioural control in the experimental group (p < .05). Sexual behaviours notably improved in the experimental group compared to controls (p < .001). TPB-based interventions effectively promote healthy sexual behaviours by enhancing knowledge and addressing social norms, fostering better decision-making among adolescents.